Kedisiplinan, Kepuasan Dan Motivasi Kerja Merupakan Penunjang Bagi Para Karyawan Perusahaan Swasta Berpendidikan Rendah Untuk Meningkatkan Prestasi Kerja Di Perusahaan - Lilik Indrawati (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2012)
The results of case studies on PT. Modern Surya Jaya Piling Division in Krian Sidoarjo East Java showed that employees with low education are less disciplined in terms of entry to and from work. The results of research in the field showed that the average employee who delayed between 5-8 people per day, and likely not the same person. Similarly, the lack of discipline in the use of work time is not optimal, no discipline in the use of fuel. The low education employees in general were satisfied with their current jobs, and tend not to want to change job, satisfied with his colleagues, as well as satisfied with the current leadership. Thelow education employees generally stated that they have sufficient income to meet basic needs, and will be even better if there is an additional income. They generally have not been able to meet the employment targets, particularly in terms of time. They also generally have not been able to think for the benefit of thecompany, which is considered only their personal interests